2020
DOI: 10.1016/j.heliyon.2020.e04314
|View full text |Cite
|
Sign up to set email alerts
|

Does psychological capital mediate the impact of dysfunctional sleep beliefs on well-being?

Abstract: Dysfunctional sleep beliefs are strongly involved in sleep difficulties, which in turn negatively predict psychological health and well-being. In contrast, psychological capital (PsyCap) is a positive cognitive resource, comprising four dimensions (hope, self-efficacy, resilience, and optimism), that positively predicts psychological well-being. Significant associations between sleep beliefs and well-being, and PsyCap and well-being are detailed; however, research on their interrelations (among sleep beliefs, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 81 publications
2
8
0
Order By: Relevance
“…Our findings also revealed the serial multiple mediating roles of PsyCap and sleep quality in the pathway from interpersonal sensitivity to depression in Chinese postgraduate students. Sleep quality was negatively affected by PsyCap in our study, which was consistent with previous research in different populations ( 42 , 43 ). The psychological capital of postgraduate students may be affected to varying degrees by interpersonal sensitivity, which may affect the quality of sleep through psychological capital, leading to depression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings also revealed the serial multiple mediating roles of PsyCap and sleep quality in the pathway from interpersonal sensitivity to depression in Chinese postgraduate students. Sleep quality was negatively affected by PsyCap in our study, which was consistent with previous research in different populations ( 42 , 43 ). The psychological capital of postgraduate students may be affected to varying degrees by interpersonal sensitivity, which may affect the quality of sleep through psychological capital, leading to depression.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, PsyCap has been shown to be a robust predictor of sleep quality ( 42 ). PsyCap may also mediate the effects of dysfunctional sleep beliefs on wellbeing ( 43 ) and the pathway from organizational justice variability to employee sleep quality ( 44 ). Currently, there is little research on the sleep quality of postgraduate students during the lockdown.…”
Section: Introductionmentioning
confidence: 99%
“…PsyCap is therefore shaped by the interaction of the resources of efficacy, optimism, hope, and resilience, which implies that these four attributes work synergistically as a higher resource, such that their predictive ability would be significantly greater when taken together than when taken separately [ 15 ]. In this regard, various studies in occupational and academic environments have shown that PsyCap predicts levels of flourishing significantly better when it is considered as a global construct [ 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the investigation of 259 COVID-19 patients, we found that their psychological capital can directly predict social alienation. Psychological capital is a positive psychological state which can buffer the negative effects of negative emotions (Sabot & Hicks, 2020). The negative correlation between psychological capital and social alienation was veri ed by the correlation analysis in patients with COVID-19 infection (p < .01).…”
Section: Demographic Characteristics Of Patients With Covid-19 Infect...mentioning
confidence: 88%